GUIDED EMPLOYMENT – RIGHTS AND OPPORTUNITIES FOR PEOPLE WITH INTELLECTUAL DISABILITIES - Erna ZHGUR (Journal of Special Education and Rehabilitation, 2017)
Introduction: People with intellectual disabilities (ID) are often excluded from the labour market and face many obstacles on their way to employment. Aim: The main aim is giving the persons with ID a possibility to participate in occasional employment, providing them suitable work skills, sustainable knowledge and competencies, as well as suitable skills for more active life. Materials and methods: We analysed 90 evaluation questionnaires (filled out by students, mentors, parents and craftsmen), during a 3-year project (September 2013 - October 2015). The Spearman Correlation Coefficient and Chi-square test were used for statistical data analysis. Results: We determined the level of satisfaction expressed by parents, mentors and students, related to guided employment (χ2 = 1,07; p > 0,05; χ2 = 0,04; p > 0,05;χ2 = 0,04; p > 0,05). Workshops were balanced with theoretical and practical content (χ2 = 16,58; p < 0,05). Mentors, parents, students and craftsmen expressed similar opinions in regards to the success of individual workshops (it depended on the type of workshop); mentors (χ2 = 16,76; p < 0,05); parents (ϱ = 0,99, p < 0,05); students (ϱ = 0,55; p > 0,05), craftsmen (ϱ = 0,79; p < 0,05). Craftsmen were willing to accept students with ID even without adapting the working conditions or state incentives (χ2 = 3,34; p > 0,05). Conclusion: Implementation of selected workshops, related to guided employment showed that employment of people with ID is possible under professional guidance of mentors.